Experimental database of mixed-mode crack propagation tests performed on mortar specimens with a hexapod and full-field measurements. Part II: interactive loading. (November 2019) - Carpiuc-Prisacari, A.; Jailin, C.; Poncelet, M.; Kazymyrenko, K.; Leclerc, H.; Hild, F.
Abstract: This second paper presents a series of 4 crack propagation tests with the same experimental protocol as in a companion paper, but with some significant loading modifications. The first difference is that the loading is composed of in-plane rotation in addition to tension and shear translations. The second difference is that the loading is manually changed during the tests, depending on the crack tip location. This leads to tests with several bifurcations, and/or different loading ratios during the same test. One of them leads to mode I+II, and then mode I+III crack propagation. Some tests end with instabilities while others are controlled to be stable up to the complete failure of the specimen. In some cases, crack closure and friction between the crack faces occur.